2012
DOI: 10.1007/s00296-012-2550-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of insomnia in chronic low back pain patients

Abstract: The purpose of this study was to assess prevalence and severity of insomnia in participants diagnosed with chronic low back pain (CLBP) and to identify factors associated with this insomnia. One hundred CLBP consenting participants were recruited. Sociodemographic, CLBP features and sleep characteristics were collected. Patients answered validated measures of insomnia severity and fatigue. Statistical analysis examined the relationship between insomnia, sociodemographic characteristics of patients and CLBP par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
72
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 20 publications
9
72
2
1
Order By: Relevance
“…Pain with any origin is only one of them. Similarly, Bahoug and his coworkers has found also moderate correlation between the pain severity and insomnia (Bahouq et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain with any origin is only one of them. Similarly, Bahoug and his coworkers has found also moderate correlation between the pain severity and insomnia (Bahouq et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Sixty four million of Americans suffer from inadequate sleep according to report of the health ministry of USA. This is 1.4 time more prevalent in women (Basics 2011;Lamberg 2007 (Alsaadi, McAuley, Hush, & Maher 2011;Bahouq, Allali, Rkain, Hmamouchi, Hajjaj-Hassouni 2013). Pain and sleep may have intricate relationship with each other.…”
Section: Introductionmentioning
confidence: 99%
“…13 Several studies have examined the association of pain and sleep disturbance and have found evidence of associations of pain with sleep quality, 11,14 reduced sleep time, 12 lower sleep efficiency, 9,11 and more awakenings. 11 All of these studies examine chronic pain, thus the relationship between acute pain and sleep disturbance is less well examined.…”
mentioning
confidence: 97%
“…[8][9][10] Thus, it is a substantial problem "adding insult to injury" for this large group of patients, perhaps contributing to a vicious cycle of maintaining pain. There is a need to understand the association of pain and sleep to improve the management of LBP.…”
mentioning
confidence: 99%
See 1 more Smart Citation